2018
DOI: 10.4172/2155-9546.1000540
|View full text |Cite
|
Sign up to set email alerts
|

Fate of [3H]-Deoxynivalenol in Rainbow Trout (Oncorhynchus mykiss) Juveniles: Tissue Distribution and Excretion

Abstract: Deoxynivalenol (DON), a Fusarium mycotoxin, is one of the most prevalent mycotoxins in aquafeeds. The toxicokinetics of DON are rarely studied in aquatic species. The present study used juvenile rainbow trout (Oncorhynchus mykiss) with a mean initial body weight of 7.72 ± 1.42 g in order to evaluate the pharmacokinetic behaviour and the metabolization of radiolabelled DON ([ 3 H]-DON). In a first trial, 30 fish were tube-fed with four pellets containing a total of 125 ± 0.019 ng of [ 3 H]-DON. At different sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 21 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…An in vivo experiment with rainbow trout confirmed metabolisation of DON to the less toxic DON-3sulfate, possibly explaining the absence of clinical signs with high doses of DON [119]. In general, also in fish, DON and its metabolites are readily excreted via the bile and thereby finally via the faeces [146]. Studies have shown almost negligible accumulation of DON in the muscle of salmon [108,147], carp [125] and gilthead sea bream [147], indicating little risk to humans after consumption of farmed fish fillet.…”
Section: Metabolic Fate Of Donmentioning
confidence: 94%
“…An in vivo experiment with rainbow trout confirmed metabolisation of DON to the less toxic DON-3sulfate, possibly explaining the absence of clinical signs with high doses of DON [119]. In general, also in fish, DON and its metabolites are readily excreted via the bile and thereby finally via the faeces [146]. Studies have shown almost negligible accumulation of DON in the muscle of salmon [108,147], carp [125] and gilthead sea bream [147], indicating little risk to humans after consumption of farmed fish fillet.…”
Section: Metabolic Fate Of Donmentioning
confidence: 94%
“…Different animals vary in their susceptibilities to DON in the order of pigs, mice, rats and poultry, which may be related to the different in absorption, distribution, metabolism and excretion of DON in animals [14]. Meanwhile, the toxicokinetics of DON have been studied on different kinds of animals, including pigs [15], chickens [16], mice [17], rats [18] and fish [19]. The time to reach the maximum plasma DON concentration (T max ) after oral administration was about 0.08-0.5 h in mice [20,21], 2 h in chicken [22] and 10 min in rats [23].…”
Section: Introductionmentioning
confidence: 99%
“…Further studies had also confirmed the impact of DON on rainbow trout productivity; either by using low DON doses (1100 and 2700 µg/kg) (Gonçalves et al, 2019) or high (4700 and 11400 µg/kg) (Gonçalves et al, 2018b). Notably, the latter study provided new insights into the direct effects of DON by measuring proteolytic enzyme activity and relevant gene expression in the head kidney, liver, brain and gastrointestinal tract.…”
Section: Rainbow Troutmentioning
confidence: 87%
“…An in vivo experiment with rainbow trout confirmed metabolisation of DON to the less toxic DON-3-sulfate, possibly explaining the absence of clinical signs with high doses of DON (Gonçalves et al, 2018b). In general, also in fish, DON and its metabolites are readily excreted via the bile and thereby finally via the faeces (Gonçalves et al, 2018b). Studies have shown almost negligible accumulation of DON in the muscle of salmon (Bernhoft et al, 2017;Nácher-Mestre et al, 2015), carp (Pietsch et al, 2014b) and gilthead sea bream (Nácher-Mestre et al, 2015), indicating little risk to humans after consumption of farmed fish fillet.…”
Section: Metabolic Fate Of Donmentioning
confidence: 92%
See 1 more Smart Citation